An Analysis of Application of Natural Language Processing in Enhancing Education (International Journal of Innovative Research in Computer Science & Technology, 2021)
NLP (Natural Language Processing) is an  intriguing technique for improving educational settings.  In educational modelling, actualizing NLP entails  beginning path toward learning via regular acquisition. It  is dependent on operative methods in providing answers  to numerous training problems. Conventional Processing  allows for organization in a broad variety of areas linked  to language learning's social & social context. It's a  proven approach for instructors, students, authors, & teachers to assist with producing, analysis, & evaluation  methods. NLPis widely used in a wide range of  educational institutions, including research, phonetics,  eLearning, & assessment modelling, & it leads to good  outcomes in or educational organizations, such as  schools, advanced education institutes, & colleges.  Purpose of this article is to discuss process of acquiring a  common language & its implementation in educational  institutions. Study approach also discusses how NLP  may be utilized in conjunction with logical PC projects to  enhance training process. Subjective approach is pursued  in research methodology. Information is collected from  auxiliary assets in order to identify problems that teachers  & students have in comprehending environment due to  language barriers. Findings show that traditional  apparatuses, such as language, sentence structure, & printed designs, are viable in educational settings for  learning & assessment.
Keywords: Acquisition; Education; Language processing; Learning; Natural Language Processing